2021
DOI: 10.14569/ijacsa.2021.0120580
|View full text |Cite
|
Sign up to set email alerts
|

Natural Language Processing Applications: A New Taxonomy using Textual Entailment

Abstract: Textual entailment recognition is one of the recent challenges of the Natural Language Processing (NLP) domain. Deep learning strategies are used in the work of text entailment instead of traditional Machine learning or raw coding to achieve new enhanced results. Textual entailment is also used in the substantial applications of NLP such as summarization, machine translation, sentiment analysis, and information verification. Text entailment is more precise than traditional Natural Language Processing technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…By utilizing this analysis technique, it will be possible to summarize the information contained in large data tables down to some smaller summary index sets or appropriate groups. Research on the efficient detection of depression from textual social content was also carried out [65] researching a similar study which later found that textual is promising when used with deep learning that applies the GRU, Bi GRU, LSTM, Bi LSTM methods the result is an accuracy of 80 %, 81%, 80%, 81%. The testing process is divided into several stages.…”
Section: Methodsmentioning
confidence: 99%
“…By utilizing this analysis technique, it will be possible to summarize the information contained in large data tables down to some smaller summary index sets or appropriate groups. Research on the efficient detection of depression from textual social content was also carried out [65] researching a similar study which later found that textual is promising when used with deep learning that applies the GRU, Bi GRU, LSTM, Bi LSTM methods the result is an accuracy of 80 %, 81%, 80%, 81%. The testing process is divided into several stages.…”
Section: Methodsmentioning
confidence: 99%
“…-In most recent studies, e cient entailment models are often used in other elds such as medicine, cooking, and recognition of depression cases [21]; [22]. In fact, domain-speci c data is ne-tuned using BERT models.…”
Section: Contradiction Relationmentioning
confidence: 99%
“…p. ex. : Bernardy & Chatzikyriakidis, 2020 ;Crouch et al, 2005 ;Dagan et al, 2013 ;Elshazly, Haggag & Ehssan, 2021 ;Liu et al, 2020 ;Paramasivam & Nirmala, 2021).…”
Section: Introductionmentioning
confidence: 99%